SECURITY AND THE 2019 ELECTIONS: Reflections from Criminology - Attoh, Franca; Okeke, Emeka Joel (Advances in Social Sciences Research Journal, 2019)
Multiparty elections have become the bellwether by which all democracies are judged and the spread of these systems across Africa has been widely hailed as a sign of the continent's progress towards stability and prosperity. But such elections bring their own challenges, particularly the often intense internecine violence following disputed results. While the consequences of such violence can be profound, undermining the legitimacy of the democratic process and in some cases plunging countries into civil war or renewed dictatorship, little is known about the causes. By mapping, analyzing and comparing instances if election violence in different localities across Africa, this collection of detailed case studies sheds light on the underlying dynamics and sub-national causes behind electoral conflicts, revealing them to be the result of a complex interplay between democratization and the older, patronage-based system of "Big man" politics.